Low Temperature Drying to Maintain the Quality of Agricultural Products - R Sarwono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Drying equipment is an important unit operation in industrial processes. Reducing moisture content in order to prolog the storage time is very commonly used. There are many agricultural product which are very heat sensitive. To maintain the essential ingredient in those product, drying process should be applied at low temperature drying process gave lower drying rate, is time consuming and in general costly. Increasing drying rate by reducing the absolute humidity is this recommended. There are many ways to dry the air, firstly moisture is condensed in evaporator and then dried air is heated in condenser. Is conducted if the drying system in connected with heat pump system. Secondly, moisture is absorbed by hygroscopic materials such as CaO. Water absorbed and reacted with CaO become Ca(OH)2 in exothermic reaction, and simultaneously dried air is heated.